Trade-Offs Underwater: Physiological Plasticity of Rainbow Trout (Oncorhynchus mykiss) Confronted by Multiple Stressors - Elena Wernicke von Siebenthal; Kristina Rehberger; Christyn Bailey; Albert Ros; Elio Herzog; Helmut Segner (Fishes, 2018)
Organisms have evolved mechanisms to partition the available resources between fitness-relevant physiological functions. Organisms possess phenotypic plasticity to acclimate to changing environmental conditions. However, this comes at a cost that can cause negative correlations or “trade-offs”, whereby increasing investments in one function lead to decreased investments in another function. The aim of the present study was to investigate the prioritization of resource allocation between growth, pathogen defense, and contaminant response in juvenile rainbow trout (Oncorhynchus mykiss) exposed to changes of resource income or expenditure. We performed a multifactorial experiment with three resource-impacting stressors—limited food availability, a parasitic infection, exposure to a vitellogenesis-inducing contaminant—and combinations thereof. Treatment with the individual stressors evoked the expected responses in the respective physiological target systems—body growth, immune system, and hepatic vitellogenin transcription—but we found little evidence for significant negative relations (trade-offs) between the three systems. This also applied to fish exposed to combinations of the stressors. This high phenotypic flexibility of trout in their resource allocation suggests that linear resource allocations as mechanisms of phenotypic plasticity may be too simplistic, but it also may point to a greater capacity of ectothermic than endothermic vertebrates to maintain key physiological processes under competing resource needs due to lower maintenance costs.